Studi Kelayakan dan Lean Canvas Hotel Universitas Padjadjaran pada Aset Cikeruh 07 Jatinangor - Muhammad Harits Maulana ElHaq; Wa Ode Zusnita Muizu; Asep Mulyana (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
Universitas Padjadjaran owns idle assets that require optimization to support fiscal independence as a state-owned legal entity higher education institution (PTN-BH). The Cikeruh 07 building in Jatinangor with a book value of Rp248.05 billion remains in unfinished condition without revenue stream. This study aims to analyze the feasibility of hotel development on the Cikeruh 07 asset and to design a Lean Canvas as an integrated business model. A qualitative descriptive method following Sugiyono's interactive analysis is applied, supported by data triangulation from three expert interviews, field observation, and document analysis. Four feasibility aspects are evaluated, namely market and marketing, technical and operational, legal and regulatory, and financial. The findings indicate feasibility on all four aspects. Market analysis identifies institutional conference hotel positioning with four-star character. Technical analysis confirms asset suitability with CAPEX Rp24.00 billion for 80 rooms. Legal analysis validates the KSP scheme based on PMK 115/2020 with a 60-year cooperation period. Financial analysis yields NPV Rp7.73 billion, IRR 26.68% exceeding Ke 13.98%, payback period 4.62 years, and PI 2.20. The Lean Canvas synthesis positions Hotel Universitas Padjadjaran as a first-mover institutional conference hotel in the Jatinangor area.